When you learn the alphabet - Allen, Kendra, 1994- (Iowa Prize in Literary Nonfiction., 2019)
"Kendra Allen's first collection of essays When You Learn the Alphabet--at its core--is a bunch of mad stories about things she never learned to let go of. Unifying personal narrative and cultural commentary, this collection grapples with the lessons that have been stored between father and daughter as well as mother and daughter. These parental relationships expose the conditioning that subconsciously informed and encouraged her ideas on social issues such as colorism, feminism, war-induced PTSD, homophobia, marriage, and 'the n-word, ' among other things"--